2017
DOI: 10.1080/10447318.2017.1379240
|View full text |Cite
|
Sign up to set email alerts
|

Balancing the Fluency-Consistency Tradeoff in Collaborative Information Search with a Recommender Approach

Abstract: Creative group work can be supported by collaborative search and annotation of Web resources. In this setting, it is important to help individuals both stay fluent in generating ideas of what to search next (i.e., maintain ideational fluency) and stay consistent in annotating resources (i.e., maintain organization). Based on a model of human memory, we hypothesize that sharing search results with other users, such as through bookmarks and social tags, prompts search processes in memory, which increase ideation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In a study that used the Social Semantic Server, we found evidence that feeding back emergent tag networks in a work‐integrated web curation scenario led to higher levels of shared understanding in the group. When recommending tags in such situation, these were more readily accepted, if the recommender services made use of the emerging category–tag relationship (Seitlinger et al, ).…”
Section: Overall Reflections and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study that used the Social Semantic Server, we found evidence that feeding back emergent tag networks in a work‐integrated web curation scenario led to higher levels of shared understanding in the group. When recommending tags in such situation, these were more readily accepted, if the recommender services made use of the emerging category–tag relationship (Seitlinger et al, ).…”
Section: Overall Reflections and Discussionmentioning
confidence: 99%
“…Tags were also seen as a way to negotiate the meaning of particular experiences and established shared understanding in a group of learners (Dennerlein, Seitlinger, Lex, & Ley, 2016). Several services made use of the tags produced, eg, recommender services for resources (Seitlinger et al, 2015) or tag recommenders that were intended to drive the consistency of how objects were described (Seitlinger et al, 2018).…”
Section: Knowledge Structuresmentioning
confidence: 99%
“…The collected data for both groups as well as for the full dataset is shown in Table 1. For details on the study design, please see [6].…”
Section: Methodsmentioning
confidence: 99%